Family cultural norms and its role in negative internet choices of children - REHIM, MASTUR; ABU-ATTIYEH, JAMAL; HUSSAIN, TAMIM (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT In the current study, it was tried to recognize the variability of family upbringing when monitoring their children to prevent exposure to the disadvantages or negatives uses of the internet. The study adopts the use of a sample-based social survey methodology. Each sample was selected on the condition that the father and mother shall have children still studying in school and using the internet. This study observes 300 families in Al-Ain, UAE.